Simulating radiation damage in Ga stabilised [delta]-Pu - Robinson, Marc; Kenny, S.; Smith, R.; Storr, M. (Elsevier, 2011)
Radiation events in Ga stablised d-Pu are investigated by means of Molecular Dynamics simulations. Pu5 at.% Ga is considered using the Modified Embedded Atom Method to govern the atomic interactions.Cascades were initiated with Primary Knock-on Atom (PKA) energies in the range of 0.4–10 keV, with trajectoriesdeduced through comprehensive sampling of a representative set of directions, combined withdifferent Ga atomic positions. The displacement threshold energy, Ed, for Pu and Ga atoms was also determinedthrough similar extensive studies to aid the understanding and interpretation of the cascaderesults.Values of Ed between 5 and 40 eV were determined for Pu, with Ga PKAs requiring generally moreenergy to create a defect with Ed between 8 and 70 eV. Low energy collision cascades, initiated with energiesin the range of 0.4–1 keV, show that the cascades form in a similar manner to other fcc metals with avacancy rich zone surrounded by isolated interstitial defects. A feature of these cascades is that the displacedGa atoms return to lattice sites during the ballistic phase, leading to a lack of Ga-type residualdefects. Higher energy cascades show similar features but with the development of an amorphous regionat the cascade core of around 5 nm diameter at 5 keV. Quantitatively, the residual number of defectsfound shows no distinct variation to that for previous work on pure Pu, suggesting the inclusion of Gadoes not significantly effect the susceptibility or resistance of Pu to initial cascade development.